ABUNDANCE AND TAXONOMIC COMPOSITION OF THE COASTAL AREA OF YEASTS OF ZMIINIY ISLAND - В. О. Іваниця; С. О. Білоіваненко (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2012)
Coastal waters for the first time Snake Island studied the number and taxonomic composition of yeast microbiota. It is shown that the number of yeast varied in a narrow range from 220½103 to 760½103 cfu/l. Research has identified 11 species of yeasts belonging to 6 genera (Cryptococcus albidus, C. neoformans, Aureobasidium pullulans, Candida albicans, C. glabrata, C. parapsilosis, C. tropicalis, Rhodotorula rubra, R. glutinis, R. m inuta, Saccharomyces cerevisiae). Identified only four members of the genus (Cryptococcus, Candida, Pichia, Rhodotorulla). Representatives of all 11 identified species are typical cosmopolitan and fairly common in other habitats of the Earth. The most common in the coastal waters of the waters of the island were the representatives of unidentified species of Rhodotorula spp., Candida spp. and the type of Rhodotorula rubra. The greatest number and taxonomic diversity of yeast found in the port area and the economic activities of inhabitants.